ANALYSIS OF CONTINUOUS QUALITY IMPROVEMENT USING WASTE ASSESSMENT MODEL AND DEMING CYCLE METHOD (STUDY CASE: TAPIOCA STARCH MANUFACTURING) - Widi Astutik; Irwan Setiawan; Sapta Asmal (Center for Study and Journal Management FTI UMI, 2022)
This study explains what waste occurs in the manufacturing industry, where there are 7 wastes, namely excess production, waiting time, unnecessary transportation, excessive processes, excess inventory, unnecessary movements, and defective products. As a result of this waste, the company has lost an output of 46 tons in 1 semester. The purpose of this research is to find out the critical waste and the source of the waste that occurs in the manufacturing industry and then reduce the waste using the waste assessment model and the deming cycle method. The method used to identify waste is the waste assessment model. The waste assessment model consists of 2 stages, namely the waste relationship matrix to determine the relationship between waste and a waste assessment questionnaire to identify the causes of waste. The results of this study obtained critical waste from 7 wastes, namely defect waste with a percentage of 27.94% and the cause of the waste is the frequency of machine breakdowns that occur in area 2 production. It can be concluded that the critical waste in this research is defect waste that originates from engine damage in the production area and within a quarter the waste has been eliminated so that it can maximize the production process.